Regulation of the Statute of Limitations in the Law of Obligations: Analysis of the Latest Amendments to the Law on Obligatory Relations and Decision of the Constitutional Court of the Republic of North Macedonia - Nikola Dacev (Societas et Iurisprudentia)
The regulation of the statute of limitations in the law of obligations, also known as the time-barring period, establishes the time frame within which legal action must be initiated to enforce obligations such as debts. These regulations are critical for ensuring legal certainty, protecting defendants from outdated claims, and promoting timely resolution of disputes. Statutes of limitations vary widely between different jurisdictions and depend on the type of obligation (if the contract is written, oral or it is promissory note and open-ended account). In the current Law on Obligatory Relations of the Republic of North Macedonia, it is stipulated that all claims determined by a final court decision, by a decision of another competent authority, or by a settlement before a court, would expire in ten years, including those for which the Law otherwise provides a shorter statute of limitations. With the amendments to the Law, the aim was for this provision to be amended by shortening the limitation period to five years from the validity of the decision (corresponding to the general limitation period for claims) because there are abuses by intentionally waiting nine years and eleven months to pass and an enforcement procedure to start, so the enforcement agents and creditors can receive compensation for interest. In this paper, the aim is to analyze the effects of the new amendments to the Law on Obligatory Relations of the Republic of North Macedonia which raised many debates but also an initiative of the Constitutional Court of the Republic of North Macedonia to assess the constitutionality of these amendments.